Digital distraction or accessible aid? Parental media use during feedings and parent-infant attachment, dysfunction, and relationship quality. (February 2022) - Coyne, Sarah M.; Shawcroft, Jane; Gale, Megan; Reich, Stephanie M.; Linder, Lisa; McDaniel, Brandon; Stockdale, Laura; Booth, McCall
Abstract: Often parents are discouraged from using media around their infants, particularly during feeding time, as media use is thought to harm the development of parent-infant attachment. Little research, however, has examined the relationship between parent media use during infant feeding and parent-infant dysfunction and attachment over time. This paper involves two separate studies (using quantitative and qualitative approaches) to examine why parents use media while feeding their infants and how media use during feeding relates to parent-infant relationships, particularly attachment. The overwhelming majority of parents (mostly mothers in this study) reported using media at least sometimes while feeding their infants. Parents reported using media to cope with the difficulties of feeding, to remain productive during feeding time, and to connect with others. Parent media use during infant feeding was not longitudinally associated with attachment, and media use during infant feeding was longitudinally linked to decreases in parent-toddler dysfunction. Overall, we believe that media may be a helpful tool to support parents (particularly mothers) cope with the difficulties of parenting infants. Limitations and other implications are discussed. Highlights: The vast majority of mothers use media while feeding their infant. Mothers report a number of adaptive reasons why they use media during feeding times. Media use while feeding was not related to attachment problems in the future. Media use while feeding was related to lower levels of parent/infant dysfunction over time.